2016
DOI: 10.1093/mnras/stw2593
|View full text |Cite
|
Sign up to set email alerts
|

On the rotation of nuclear star clusters formed by cluster inspirals

Abstract: Nuclear Star Clusters (NSCs) are commonly observed in the centres of most galactic nuclei, including our own Milky Way. While their study can reveal important information about the build-up of the innermost regions of galaxies, the physical processes that regulate their formation are still poorly understood. NSCs might have been formed through gas infall and subsequent in situ star formation, and/or through the infall and merging of multiple star clusters into the centre of the galaxy. Here, we investigate the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 47 publications
2
77
0
Order By: Relevance
“…The presence of the young stellar disc as well as the existence of H ii regions and young stars within the central 100 pc of the Milky Way (Figer et al 2004) suggest that the GC went through recent star formation processes in this region (Genzel et al 2010). However, while the majority of current studies focused on the understanding of the build-up of NSCs through the infall of stellar clusters (Tremaine et al 1975;Capuzzo-Dolcetta 1993;Antonini et al 2012;Arca-Sedda & Capuzzo-Dolcetta 2014;Mastrobuono-Battisti et al 2014;Gnedin et al 2014;Arca-Sedda et al 2015;Antonini et al 2015;Arca-Sedda & Capuzzo-Dolcetta 2017a,b;Tsatsi et al 2017;Abbate et al 2018), very few studies so far explore the long-term effects and evolution of NSCs with insitu star formation (Aharon & Perets 2015;Guillard et al 2016;Baumgardt et al 2018). In particular the potential insitu star formation producing stellar discs such as the one observed in the GC had not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the young stellar disc as well as the existence of H ii regions and young stars within the central 100 pc of the Milky Way (Figer et al 2004) suggest that the GC went through recent star formation processes in this region (Genzel et al 2010). However, while the majority of current studies focused on the understanding of the build-up of NSCs through the infall of stellar clusters (Tremaine et al 1975;Capuzzo-Dolcetta 1993;Antonini et al 2012;Arca-Sedda & Capuzzo-Dolcetta 2014;Mastrobuono-Battisti et al 2014;Gnedin et al 2014;Arca-Sedda et al 2015;Antonini et al 2015;Arca-Sedda & Capuzzo-Dolcetta 2017a,b;Tsatsi et al 2017;Abbate et al 2018), very few studies so far explore the long-term effects and evolution of NSCs with insitu star formation (Aharon & Perets 2015;Guillard et al 2016;Baumgardt et al 2018). In particular the potential insitu star formation producing stellar discs such as the one observed in the GC had not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Strong rotation is seen in nearby nuclear star clusters (Seth et al 2008b;Seth 2010;Feldmeier et al 2014;Nguyen et al 2017), with V s values ranging between ∼0.3 and 1.3, with both early and late-type galaxies showing strong rotation. This rotation can be created through cluster merging, but the strongest rotation is likely to be due to in situ star formation (e.g., Hartmann et al 2011;Tsatsi et al 2017). Larger scale (∼100 pc) nuclear disks are also common (Launhardt et al 2002;Balcells et al 2007;Chilingarian 2009;Morelli et al 2010;Toloba et al 2014), and stripping of these could also yield rotating UCDs.…”
mentioning
confidence: 99%
“…This finding was confirmed by Fritz et al (2016). In addition, the line-of-sight velocity map shows a perpendicular rotating substructure, which may be the result of star cluster infall (Feldmeier et al 2014;Tsatsi et al 2017). In summary, the Milky Way appears to contain a rather typical example for an NSC, because many of its properties are entirely consistent with the general sample of NSCs in external galaxies (see also Table 2).…”
Section: Properties Of the Milky Way Nuclear Star Clustermentioning
confidence: 65%
“…In a similar vein, successfully reproduced the density profile of the Milky Way NSC from the accretion of globular clusters, but also concluded that the observed luminosity function requires younger stars and therefore suggested that only about half the NSC mass can originate from globular cluster inspirals. The rotation of NSCs was investigated by Tsatsi et al (2017), who found that their models could match the observed flattening (Schödel et al 2014a), and rotation signature (Feldmeier et al 2014) of the Milky Way NSC (Figs. 10 and 11).…”
Section: Globular Cluster Infall and Mergingmentioning
confidence: 99%